Discurso pedagógico na educação permanente em saúde: estudo de curso de Educação a Distância no Ensino Superior - Carvalho, Paulo Jorge de Oliveira (2018)
This work deals with the pedagogic discourse in Distance Higher Education focusing on the Permanent Education in Health. The general goal is based on the reflection about the use of digital technologies while structuring the pegagogic discourse in distance Higher Education to analyze underlying mechanisms in the pedagogical practices developed in virtual learning environments, and having as the study’s object the post-graduation course (specialization) EPS em Movimento. The research topic questions the characteristics of the pedagogic discourse in Distance Higher Education courses and analyzes the work in a course of permanent education that comes from the students’ knowledge. For the characterization and analysis of these pedagogical practices, this work used as the main methodological and theoretical reference, the theory of Basil Bernstein based on the concepts of code, classification and framing, specifically in the aspects that concern the established relations among subjects, discourses and spaces in regulating and instructional contexts of the pedagogic discourse. The work is based on the hypothesis of the existence of a weak framing without previous definitions of content, organization/sequence and the way the students work, strong defining classification of contents – which were confirmed in the results – as well as weak framing in relation to evaluation criteria that were partially confirmed. It is a documental research, conducted according to a mixed approach of investigation that associates qualitative and quantitative aspects regarding the approximation of investigation through the analysis of the virtual environment of the course hosted on Plataforma para Comunidades de Prática (OTICS) (in English: Platform for Communites of Practices). The data collection was composed of documents that compose the structure of the course about administrative and regulatory aspects, besides pedagogical material and teaching/learning practices registered on the integration forums. The obtained results demonstrated, in general, similar characteristics in both contexts. In the instructional content the control over communication in the learning process of the three related abilities developed in the course - responsibility, cooperation and autonomy - was centered in the students who conducted the selection and presentation sequence of the contents, as well as the acquisition period. The evaluation criteria presented variations in relation to the clarity of what was expected from the students and in the relation between discourses. An absence of interconnection was observed between the contents of the abilities and the promition of EPS. The regulating context was characterized by interpersonal communication relations which were open and democratic between tutor and students and also among students. In relation to the spaces occupied in the virtual learning environment, well-established frontiers between the students and the tutors were identified and sharing of free spaces among the students